The Islamic Lifestyle of the Muslim Middle Economy Class and the Opportunities for the Halal Tourism Industry in Indonesia - Muheramtohadi, Singgih; Fataron, Zuhdan ady (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
In the last two decades there have been several social changes, such as the rise of industries based on sharia provisions from banking products, cosmetics, as well as Sharia tourism. Along with this growth, there have also been changes in attitudes and lifestyles such as the widespread use of the hijab which is often called the hijab revolution. This does not only occur in the lower economic class but also in the middle economic class. The economic lifestyle of the Muslim middle class also affects the demand for halal products. This paper aims to explain the relationship between the lifestyle of the Muslim economic middle class and its relationship with the opportunities for the halal tourism industry in Indonesia. The research method used is qualitative with a literature study and a descriptive approach. The results of this study are the relationship between middle class status, lifestyle and sharia products in Indonesia is very close. Halal tourism is also part of an industry that seeks to capture the opportunities generated by this market. Seeing the relationship between the middle class and the opportunities possessed by Halal Tourism is very large, and in the future it is expected that various industries that support sharia tourism will emerge, from lodging, restaurants, to various types of culinary delights that adapt to the needs of the Muslim middle class, which is always growing from year to year.